2007
DOI: 10.1002/ibd.20059
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic overlap between irritable bowel syndrome and microscopic colitis

Abstract: In this population-based cohort of histologically confirmed microscopic colitis, approximately one-half met symptom-based criteria for the diagnosis of irritable bowel syndrome. The clinical symptom-based criteria for irritable bowel syndrome are not specific enough to rule out the diagnosis of microscopic colitis. Therefore, patients with suspected diarrhea-predominant irritable bowel syndrome should undergo biopsies of the colon to investigate for possible microscopic colitis if symptoms are not well control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(87 citation statements)
references
References 52 publications
4
79
2
2
Order By: Relevance
“…There were four studies reporting the prevalence of IBS symptoms in patients with MC, 41,44,48,49 two of which were case series, 44,48 one a case-control study, 49 and one a cross sectional survey. 41 There were three cross-sectional surveys reporting the prevalence of MC in patients with IBS, 14,41,42 one of which also reported the prevalence of IBS in patients with MC and was included in the aforementioned analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were four studies reporting the prevalence of IBS symptoms in patients with MC, 41,44,48,49 two of which were case series, 44,48 one a case-control study, 49 and one a cross sectional survey. 41 There were three cross-sectional surveys reporting the prevalence of MC in patients with IBS, 14,41,42 one of which also reported the prevalence of IBS in patients with MC and was included in the aforementioned analysis.…”
Section: Resultsmentioning
confidence: 99%
“…41,44,48,49 Detailed characteristics of these studies are provided in Table 1. To define IBS, three studies used the Rome II criteria, 44,48,49 and one used the Rome III criteria.…”
Section: Prevalence Of Ibs Symptoms In Patients With MCmentioning
confidence: 99%
See 2 more Smart Citations
“…It is described that MC impairs health-related quality of life (HRQOL) [6]. Several studies have shown a symptomatic overlap between MC and irritable bowel syndrome (IBS) [7,8], and the combination of these two diseases further impairs gastrointestinal symptoms and psychological well-being [8]. The great overlap between IBS and MC, the fact that 63% of MC patients only have a single attack of diarrhoea, and the wide range of conditions rendering secondary MC, may lead to an inaccurate diagnose-setting [1,3,9].…”
Section: Introductionmentioning
confidence: 99%